ChemInform Abstract: Heteroanellated and 7‐Deoxygenated Goniofufurone Mimics with Antitumor Activity: Design, Synthesis and Preliminary SAR Studies. Issue 9 (4th March 2014) - Popsavin, Velimir; Francuz, Jovana; Zelenovic, Bojana Sreco; Benedekovic, Goran; Popsavin, Mirjana; Kojic, Vesna; Bogdanovic, Gordana
Abstract New compounds (II) and (III) show diverse growth inhibitory effects against selected tumor cell lines, but are devoid of any significant toxicity towards the normal foetal lung fibroblasts.